Szopka polityczna Minkiewicza i Brzechwy. (Gdynia : [s.n.], 1946)
Afisz inf. o szopce.
Keywords: Życie artystyczne -- Polska -- Sopot -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- druki ulotne